Abstrakt interacts with and regulates the expression of sorting nexin-2 - Abdul-Ghani, Mohammad; Hartman, Kristin L.; Ngsee, Johnny K. (Journal of cellular physiology, 2005)
Protein sorting through vesicular compartments is highly regulated to maintain the integrity and signaling of intracellular organelles in eukaryotic cells. Sorting Nexin‐2 (SNX2) is involved in protein sorting in the trans‐Golgi network, endosome, and/or lysosome compartments, with loss of function leading to defect in protein sorting and stress on organelles. To investigate the function of SNX2, we have identified the DEAD‐box helicase Abstrakt (Abs) as an SNX2‐interacting protein. The N‐terminal domain of Abs interacts with the phox homology (PX) domain of SNX2 suggesting that PX domains may also participate in protein–protein interaction. Interestingly, both proteins undergo nucleocytoplasmic shuttling, and this process is responsive to serum withdrawal for Abs. Finally, expression of Abs reduced the cellular expression of SNX2 without altering its steady state mRNA levels. This unexpected interaction provides a novel mechanism whereby expression of proteins involved in membrane trafficking could be regulated by an RNA helicase. © 2005 Wiley‐Liss, Inc.